Tectônica da região nordeste do Estado de Roraima - COSTA, José Augusto Vieira (Universidade Federal do Pará, 2023)
This thesis was developed in the northeast region of the State of Roraima, comprising part of the municipalities of Normandia and Uiramutã and is part of the Guianas Shield. The geological scenario includes a wide diversity of lithological units of Proterozoic, Mesozoic and Cenozoic ages, tectonically related to the evolution of the northern sector of the Amazon Platform, stabilized at the end of the Transamazonian Cycle (2,100 Ma). Important platform reactivation events characterize the evolution of the region. The Lower / Middle Proterozoic boundary is marked by the reactivation of the structures of the Central Guiana and Parima Belts based on regional uplift followed by extensional movements, which are linked to magmatism characterized by acidic-intermediate volcanic rocks (Surumu Group - 2006 ± 4 Ma) and by intrusions of granitic rocks (Saracura Intrusive Suite - 1917 ± 38 Ma). Then, regional compression occurred around 1,860 Ma, accompanied by dynamic metamorphism that resulted in the installation of shear zones from the reactivation of normal faults, oriented in the WNW-ESE and E-W directions, characterized by mylonitic foliation with dips around 65º and subvertical in the south and central-north sectors of the area, respectively, strongly developed in volcanic and plutonic rocks, under thermal transition conditions of high greenschist and low amphibolite facies at a depth of at least 5 km and reaching temperatures around 550º C. This event accounts for the weak inversion of the basin that hosted the rocks of the Surumu Group, resulting in uplift with relief formation and consequent erosion. Around 1,800 Ma to 1,600 Ma, there is a record of another distensive episode, which reactivated the E-W direction structures that limited the northern edge of the occurrence of Surumu Group rocks, which was responsible for the disposition of the polymictic conglomeratic sandstones of the Arai Formation, sheltered at the base of the Roraima Supergroup and deposited in an alluvial fan-type continental environment, which evolved into a “braided” intertwined fluvial system with an associated wind system. The maximum age of the Arai Formation is attributed to the end of the inversion followed by erosion of the basin that housed the rocks of the Surumu Group, which would be around 1,860 Ma. The minimum age was established by the basic bodies (Diabásio Avananero) housed in the middle of the sedimentary rocks with an age of 1,805 Ma. At the end of the Roraima Supergroup sedimentation (~ 1,600 Ma) the region began to experience a period of stability. Around 1,200 Ma a tectonic event of a ductile-ruptile transpressive character (K'Mudku) occurred in the region, which reactivated the preexisting structures, mainly those located in the areas of passage of the Surumu Group and Roraima Supergroup. This event was responsible for the generation of transpressive shear zones, duplication of layers and folds related to a low-angle imbedded system with mass transport from NNW to SSE, projecting the sedimentary rocks of the southern edge of the Roraima basin onto the volcanic rocks of the Group Surumu. Possibly, throughout the Upper Proterozoic and Paleozoic, the region was stable, experiencing extensional tectonic activity only in the Mesozoic, linked to the extensional tectonics that resulted in the formation of the Atlantic Ocean. This event is expressed in the area through dykes oriented in the NE-SW direction (subparallel to the Tacutu Graben) and attributed to the Apoteri Basic Suite. The Cenozoic is characterized by the reactivation of ancient structures, as well as the development of new discontinuities from the Miocene onwards, in which the E-W, NW-SE and NE-SW directions correspond to strike-slip faults, normal faults and reverse faults, respectively, related to the dextral torque imposed on the South American Plate, as well as its interaction with the Caribbean Plate. The neotectonic reactivation produced mountainous relief, with the formation of fault scarps, cuestas, inselbergs, control of the drainage network, in addition to the deposition and reworking of sub-recent sedimentation. The current geological scenario is characterized by structural control of the drainage network, erosional processes leading to the retreat of the slopes, formation of modern alluvial deposits, as well as the incidence of periodic earthquakes.